Type-preserving compilation for end-to-end verification of security enforcement - Chen, Juan; Swamy, Nikhil; Chugh, Ravi (ACM SIGPLAN Conference on Programming Language Design and Implementation (PLDI) 2010, 2010)
A number of programming languages use rich type systems to verify security properties of code. Some of these languages are meant for source programming, but programs written in these languages are compiled without explicit security proofs, limiting their utility in settings where proofs are necessary, e.g., proof-carrying authorization. Others languages do include explicit proofs, but these are generally lambda calculi not intended for source programming, that must still be compiled further to be executable on real computers. A language suitable for source programming backed by a compiler that enables end-to-end verification is missing. In this paper, we present a type-preserving compiler that translates programs written in Fine, a source-level functional language with dependent refinements and affine types, to DCIL, a new extension of the .NET Common Intermediate Language. Fine is type checked using an external SMT solver to reduce the proof burden on source programmers. We extract explicit LCF-style proof terms from the solver and carry these proof terms in the compilation to DCIL, thereby removing the solver from the trusted computing base. Explicit proofs enable DCIL to be used in a number of important scenarios, including the verification of mobile code, proof-carrying authorization, and evidence-based auditing. We report on our experience using Fine to build reference monitors for several applications, ranging from a plugin-based email client to a conference management server.